Diskurs i stilʹ: socialʹnoe i èstetičeskoe izmereniâ teksta - Klušina, Natalʹâ I. (Stylistyka, 2020)
There are two imporlant areas in modern Linguistics: traditional stylistics and discourse studies. We need identify their common interests and differentiate them. They both find out text, context, genre. But traditional stylistics find out these categories as mental and aesthetic phenomena, and discourse studies - as pragmatic and sociál.